Horse manure derived nitrogen-doped porous carbon via hydrothermal carbonization for promising applications - Liamprawat, Tanatorn; Verasarut, Panupong; Kaewtrakulchai, Napat; Panomsuwan, Gasidit; Fuji, Masayoshi; Eiad-Ua, Apiluck (My University, 2020)
Horse manure, organic waste from livestock, has been used for the production of nitrogen-doped porous carbons (NPC) which could be applied as functional material. The variety of different NH4OH solution concentrations (0.5, 1, 1.5, 2 M) were introduced in hydrothermal treatment as activating agent. Also, the nitrogen precursor was served. Horse manure derived NPC were characterized through varied physicochemical properties including NPC yields, FTIR, SEM, XPS and N2 sorption analyzer to characterize specific properties such as elemental composition on surface, surface functional bonding, physical morphology, and porosity of NPC. In addition, the incorporation of nitrogen dopant into the carbon was intended to further enhance the electrochemical performance.
Keywords: Electrochemical performance; Horse manure; Hydrothermal Carbonization; Nitrogen-doped porous carbon